The new imperialism : crisis and contradictions in North--South relations - Biel, Robert, 1945- (London : Zed Books, 2000)
This volume seeks to deepen our understanding of the complex and constantly evolving ways in which modern capitalism, in the age of globalisation, works. It explains and illuminates the processes, institutions and policies involved.
Capital development in historical context -- Imperialism and the issue of large-scale changes in capitalism -- The post-Second World War Era -- Development theory versus practice -- The Socialist challenged to development -- The Third World challenge -- Realities overlooked: women's labour and nature -- New technologies and new management systems to the rescue? -- The role of the capitalist centre within the current phase of the international political economy -- From periphery to centre? The newly industralising country (NIC) strategy -- Permanent subordination? Structural adjustment as control -- Political implications of the new economic order -- Globalisation versus regionalism -- Future challenge: grassroots movements and the prospects for a new social order.
Includes bibliographical references (p. 328-347) and index.
Koleksi Sumbangan : Dr. Syed Husin Ali
Keywords: Capitalism; Developing countries -- Dependency on foreign countries; Competition, International